HUBUNGAN KEKERASAN VERBAL ORANG TUA DENGAN TINGKAT KEPERCAYAAN DIRI REMAJA DI SMP NEGERI 06 KOTA JAMBI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Adolescence is a critical developmental period characterized by significant physical, emotional, and psychosocial changes, in which psychological well-being is strongly influenced by the family environment. Parental communication patterns play an essential role in shaping adolescents’ self-concept and self-confidence. Negative communication in the form of parental verbal abuse, such as yelling, insulting, belittling, or using harsh words, can have long-term adverse effects on adolescents’ psychological development. This study aimed to examine the relationship between parental verbal abuse and the level of self-confidence among adolescents at SMP Negeri 06 Kota Jambi. This study employed a quantitative analytical design with a cross-sectional approach. A total of 102 students were selected as respondents using proportionate stratified random sampling. Data were collected using the Parental Verbal Abuse Questionnaire (PVAQ) to assess parental verbal abuse and a self-confidence questionnaire to measure adolescents’ self-confidence. Both instruments had been tested for validity and reliability. Data analysis was conducted using Kendall’s Tau correlation test with a significance level of p < 0.05. The results showed that the majority of respondents experienced a moderate level of parental verbal abuse (57%) and had a moderate level of self-confidence (73%). Statistical analysis revealed a significant negative correlation between parental verbal abuse and adolescents’ self-confidence (p < 0.001; τ = –0.379), indicating that higher levels of parental verbal abuse were associated with lower levels of self-confidence among adolescents. These findings highlight the importance of positive parental communication and supportive parenting practices to promote healthy psychological development in adolescents.